The Effectiveness of Telemidwife-Based ‘Permisi Gandu’ Alarm for Monitoring Adherence to Iron Supplements Consumption and Increased Haemoglobin Levels in Anemia Adolescent - Zulisa, Eva; Fuady, Khairul; Handiana, Cut Mainy (Indonesian Journal of Global Health Research, 2024)
Anemia is still a health problem for adolescent and is related to nutrition due to iron deficiency during menstruation. This is because adolescent don't like the smell of iron supplements, forget to take them, are worried about experiencing side effects, and even feel they don't need to take iron supplements. The aim of this research is to determine the effectiveness of telemidwife-based 'PERMISI GANDU' (Pengatur Minum Suplemen Zat Besi Gabung Nipis dan Madu) alarm for monitoring adherence to iron consumption and increased hemoglobin levels in anemia adolescent. The type of research is Quasi-experiment with One group pre-posttest design. The sample was taken using a Purposive sampling technique with a sample size of 36 people in Kecamatan Terangun Kabupaten Gayo Lues. Respondents were given iron supplements and lime infused water mixed with honey once every week for a duration of 4 months. Data collection on consumption compliance uses an observation form combined with video calls by midwives. For the intervention consumption schedule, the Google Calendar setting on the respondent smartphone was used as a reminder alarm. Measurement of hemoglobin levels before and after intervention using a digital hemoglobinometer. Data analysis using the Wilcoxon test. The statistical test results obtained p-value < 0.05, indicating that the telemidwife-based 'PERMISI GANDU' alarm was effective in increasing compliance with iron consumption and hemoglobin levels in anemia adolescent.